When Past Group Events and Identities Define the Present: Effect of Perceived Collective Continuity on Defensive Behaviors of the French In-Group. (April 2021) - Maoulida, Haifat; Tavani, Jean Louis; Urdapilleta, Isabel
Previous studies have highlighted the benefits of perceived collective continuity. However, to the authors' knowledge, none have considered the negative effects of such perceptions when they concern a negative past or take the form of a break with a positive past. The authors therefore conducted three studies to examine the influence of perceived continuity (or a break) with positive versus negative events or identities on French in-groups' defensive behaviors (i.e., perceptions of and attitudes toward refugees and intention to engage in collective actions). They expected to observe the positive impact of a positive (rather than negative) past continuity and a negative (rather than positive) past break. The results of Experiment 1 partially confirmed this hypothesis, as individuals who identified strongly expressed a greater intention to engage in collective actions when they perceived continuity with positive past events. Similarly, participants were more opposed to the reception of refugees when they perceived continuity with a positive past French identity (Experiment 2). Finally, high-identifier participants who perceived a break with a negative past identity expressed greater opposition to the reception of refugees and saw them more as a threat (Experiment 3). The authors discuss the importance of considering the emotional valence of past group memories for the continuity literature and a better comprehension of actual in- and between-group dynamics.